EHealth for neonatal nurse education despite Covid-19. Issue 3 (June 2021) - Cunningham, Colette; Moore, Zena; Connor, Tom O.; Patton, Declan; Bux, Dr Dhani; Nugent, Dr Linda
Abstract: Aim: The aim of this contemporary issue paper is to challenge the premise that the term "eHealth" is relatable to patient or service users only. It will be critically explored if the term can be broadened to include neonatal nurse education interventions. Design: A review of current literature will form the basis for the critical discussion of the term eHealth, and why it can be associated with neonatal nurse education. Methods: The critical discussion will identify and review past and current literature relating to eHealth and its origins. It will portray the viability of the term eHealth as more than just a patient associated intervention, and why it should also be encompassed as a neonatal nurse education option. Conclusion: eHealth is traditionally identifiable as a service user intervention or source of information. The term should be broadened to encompass neonatal nurse education and used as a resource that is easily accessible and user friendly. This will in turn encourage the personal and professional development of neonatal nurses and should ultimately contribute to evidence based best practices in the clinical environment, despite the current global pandemic.